Zinc and Growth with Picky Eating in a Jordan Pediatric Clinic: An Observational Study: Zinc and growth in pediatric with picky eating - Tarawneh, Amjad; Al-Dhmour, Haitham; Almajali, Rami; Sawaqed, Fadi; Al-Dmour, Aseel; Mahgoub, Samir (Jordan Medical Journal, 2024)
Background: Picky eating is a common feeding disorder in early childhood, characterized by a refusal to eat familiar foods or try new ones. This disorder can lead to nutritional deficiencies as well as impacting growth and development. The study aimed to determine whether picky eating is related to low serum zinc levels and growth in southern Jordan. Methods: Data collection was based on history taking and the physical examination of all examined patients at the pediatric clinic of Al-Karak Teaching Hospital. The collected data included hair loss, other signs of zinc deficiency, weight for age (Z-score), income category of the family, and the presence of underlying diseases. Blood levels of zinc, vitamin D, ferritin and hemoglobin were determined, and the results were analyzed statistically using ANOVA and t-tests. Results: An association was found between low serum zinc levels and low weight for age Z-scores, confirming the relationship between zinc deficiency and underlying general nutritional deficiencies, such as celiac disease and acrodermatitis enteropathica, which were rare (4 out of 118 studied cases); however, these patients had severely low serum zinc levels compared to the nutritional causes. On the other hand, the income category of the patient’s family could not reliably predict low serum zinc levels. Conclusion: Picky eating is associated with lower weight for age, hemoglobin levels, and vitamin D levels, thereby suggesting that picky eating can lead to a wide range of nutritional deficiencies beyond just zinc deficiency.